Adenosine A2A Receptor Deletion Blocks the Beneficial Effects of Lactobacillus reuteri in Regulatory T-Deficient Scurfy Mice - He, Baokun; Hoang, Thomas K.; Tran, Dat Q.; Rhoads, Jon Marc; Liu, Yuying (Frontiers in Immunology, 2017)
The lack of a functional Foxp3 transcription factor and regulatory T (Treg) cells causes lethal, CD4+ T cell-driven autoimmune diseases in scurfy mice and humans. Recent studies have shown that adenosine A2A receptor activation limits inflammation and tissue damage, thereby playing an anti-inflammatory role. However, the role of adenosine A2A receptor in the development of disease in scurfy mice remains unclear. Using a genetic approach, we found that adenosine A2A receptor deletion in scurfy mice (SF·A2A-/-) does not affect the early life events, the development of a lymphoproliferative disorder, or hyper-production of proinflammatory cytokines seen in the Treg-deficiency state. As shown previously, Lactobacillus reuteri (L. reuteri) treatment prolonged survival and reduced multi-organ inflammation in scurfy mice. In marked contrast, A2A receptor deletion completely blocked these beneficial effects of L. reuteri in scurfy mice. Altogether, these results suggest that although absence of the adenosine A2A receptor does not affect the development of disease in scurfy mice, it plays a critical role in the immunomodulation by L. reuteri in Treg deficiency disease. L. reuteri and adenosine A2A receptor activation may have a role in other Treg dysfunction-mediated autoimmune diseases and in the mechanism of action of other probiotics.